Machine learning-based prediction of acute mortality in emergency department patients using twelve-lead electrocardiogram - Chang, Po-Cheng; Liu, Zhi-Yong; Huang, Yu-Chang; Hsu, Yu-Chun; Chen, Jung-Sheng; Lin, Ching-Heng; Tsai, Richard; Chou, Chung-Chuan; Wen, Ming-Shien; Wo, Hung-Ta; Lee, Wen-Chen; Liu, Hao-Tien; et al. (Frontiers in Cardiovascular Medicine, 2023)
The risk of mortality is relatively high among patients who visit the emergency department (ED), and stratifying patients at high risk can help improve medical care. This study aimed to create a machine-learning model that utilizes the standard 12-lead ECG to forecast acute mortality risk in ED patients.: The database included patients who visited the EDs and underwent standard 12-lead ECG between October 2007 and December 2017. A convolutional neural network (CNN) ECG model was developed to classify survival and mortality using 12-lead ECG tracings acquired from 345,593 ED patients. For machine learning model development, the patients were randomly divided into training, validation and testing datasets. The performance of the mortality risk prediction in this model was evaluated for various causes of death.Results: Patients who visited the ED and underwent one or more ECG examinations experienced a high incidence of 30-day mortality (18,734 [5.42%]). The developed CNN model demonstrated high accuracy in predicting acute mortality (hazard ratio 8.50, 95% confidence interval 8.20-8.80) with areas under the receiver operating characteristic (ROC) curve of 0.84 for the 30-day mortality risk prediction models. This CNN model also demonstrated good performance in predicting one-year mortality (hazard ratio 3.34, 95% confidence interval 3. 30-3.39). This model exhibited good predictive performance for 30-day mortality not only for cardiovascular diseases but also across various diseases.The machine learning-based ECG model utilizing CNN screens the risks for 30-day mortality. This model can complement traditional early warning scoring indexes as a useful screening tool for mortality prediction.